Les arts de la couleur en Grèce ancienne... et ailleurs - Jockey, Philippe (Suppléments du BCH, 2018)
It is widely assumed nowadays that colours and gold played a major role in ancient Greek societies throughout the centuries. This Greek passion for colouring concerned any kind of production (clothes, glasses, make up, sculpture, monuments and so on), on any support and involving any aspect of life, death included. What do we really know about these Arts of colouring, their successful materials and processes themselves? Can we estimate their economic and social impact? Let's assume also some urgency in reevaluating our aesthetic perception of Ancient Greek Art taking into account such a polychrome revolution. Did any colourless process exist in some way? Were colours daughters of Illusion, especially in their political use? All these items are openmindedly explored in this book by means of different interdisciplinary ways, involving specialists from different scientific fields, archaeologists, architects, chemists, curators, historians, art historians and conservators. To enlighten this unique Greek experience of colouring, we compared it with other experiences led by other cultures and religions in different times: Etruscans, Romans, during the medieval period, the Renaissance and in present days.